2017
DOI: 10.3892/or.2017.5636
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of CREB1 inhibits tumor growth of human gastric cancer in vitro and in vivo

Abstract: cAMP responsive element binding protein 1 (CREB1) gene, has been reported to play crucial roles in tumor progression and development in various types of cancer. Little is known, however, about its role and underlying mechanism in gastric cancer (GC). Herein, we investigated the biological roles and molecular mechanism of CREB1 in GC. The expression level was determined in four GC cell lines by quantitative RT-PCR and western blotting. Recombinant expression vector carrying small interfering RNA (siRNA) targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…A previous report has indicated that CREB1 acts as an oncogene in GC; specifically, miRNA-122 inhibits proliferation and invasion in gastric cancer by targeting CREB1 [24]. Knockdown of CREB1 inhibits tumor growth of human gastric cancer in vitro and in vivo [25]. In the current study, using predictive tools and luciferase reporter gene assay analysis, we demonstrated that CREB1 is a target of miR-590-3p in GC cells.…”
Section: Discussionsupporting
confidence: 57%
“…A previous report has indicated that CREB1 acts as an oncogene in GC; specifically, miRNA-122 inhibits proliferation and invasion in gastric cancer by targeting CREB1 [24]. Knockdown of CREB1 inhibits tumor growth of human gastric cancer in vitro and in vivo [25]. In the current study, using predictive tools and luciferase reporter gene assay analysis, we demonstrated that CREB1 is a target of miR-590-3p in GC cells.…”
Section: Discussionsupporting
confidence: 57%
“…Analogously, studies have reported that inositol-6 phosphate (IP-6) and lncRNA UBE2CP3-001 inhibit apoptosis in some cancers [29,30]. Furthermore, CREB1 overexpression is associated with increased cell proliferation and decreased apoptotic sensitivity [31,32]. In our study, cell viability was increased and apoptosis was decreased when CREB1 was overexpressed in the RB cell model, which is consistent with the findings from Qian et al on malignant glioma cells [26].…”
Section: Discussionsupporting
confidence: 92%
“…Zhang et al reported that CREB1-induced histone H3 acetylation facilitates the transition of G0 to S phase cells in prostate cancer [34]. In addition, CREB1 has been reported to be able bind to the promoters of cell cycle genes, including cyclin A, B1, D1, D2 and Wnt10b and regulates the transcription of these genes, thereby regulating cell proliferation [31,35]. Similarly, this study revealed that miR-133a-3p prevented the transition from G1 to S phase in Y97 cells, causing cell cycle arrest and down-regulation of cyclin B1 and D1.…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 is a target of miR-495-3p and positively correlated with the advanced tumor node metastasis stage of GC [66]. Furthermore, UCA1 could sponge the miR-590-3p targeting cyclic adenosine monophosphate response element-binding protein 1 (CREB1), and knockdown of CREB1 inhibits the growth of human GC in vitro and in vivo [67,68]. Moreover, UCA1 increased multi-drug resistance of GC by downregulating miR-27b [69].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%